Faktor Keuangan mempengaruhi Nilai Perusahaan pada Subsektor Retail di BEI - Ketty Novelina Tarigan; Erika Jimena Arilyn; A Sri Wahyudi (Media Bisnis, 2023)
This study was conducted to see the effect of profitability, company growth, company size, liquidity, leverage, and dividend policy on firm value. The sample used in this study were listed companies in the wholesale sub-sector on the Indonesia Stock Exchange for the period 2007-2021 and used purposive sampling as a sampling method. With this method, there are 8 companies that meet the sampling criteria and are selected as samples with a total of 120 data. The research method used in this study is descriptive statistics and panel data regression, with the common effect model chosen. The result of this study indicate that company growth, company size, liquidity, leverage, and dividend policy do not effect the firm value. Meanwhile, profitability effects the firm value.